2015
DOI: 10.1111/jfr3.12162
|View full text |Cite
|
Sign up to set email alerts
|

The EU floods directive in Sweden: opportunities for integrated and participatory flood risk planning

Abstract: This study analyses the implementation of the EU Floods Directive in Sweden. The question here centres on the possibilities promoted by the directive for sustainable flood risk management, with an emphasis on integrated and participatory management forms. Key persons are interviewed, using a set of criteria for sustainable river basin management as a theoretical framework. The study shows that work in this area is guided by a wide array of values, and that the involved experts provide a broad knowledge basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Against the above, we find that the influence of experts on flood risk governance can best be understood as being "socially embedded" [131] or "contextually embedded" [36]. The notion of "social embeddedness" [131] emphasizes that "expertise and evidence [need to be seen as] socially embedded in authority relations and cultural contexts" (p. 259).…”
Section: Cross-case Comparison and Discussionmentioning
confidence: 82%
“…Against the above, we find that the influence of experts on flood risk governance can best be understood as being "socially embedded" [131] or "contextually embedded" [36]. The notion of "social embeddedness" [131] emphasizes that "expertise and evidence [need to be seen as] socially embedded in authority relations and cultural contexts" (p. 259).…”
Section: Cross-case Comparison and Discussionmentioning
confidence: 82%
“…A full account of the method used to apply the Sustainable Procedure Framework to the analysis of the procedures of implementing the EU Floods Directive in Sweden is provided by Hedelin (2015a). The FD study was based on interviews with the key persons responsible for designing and leading the work of the FD in Sweden at the national and regional levels:…”
Section: Case Study Methodsmentioning
confidence: 99%
“…For example, it has been shown that the implementation of the WFD and the FD is characterised by ambiguous and heavily overlapping mandates, unbalanced administrative and operational powers and democratic deficits (Hammer et al 2011;Hedelin and Lindh 2008;Hedelin 2015b;Lundqvist 2004). Through the directives, there has been a movement from local representative democratic decisionmaking towards regional expert-based decision-making ( (Hedelin and Lindh 2008;Hedelin 2015b). Furthermore, a key problem identified is that the WFD does not support explicit handling of value trade-offs related to water management decisions (Hedelin 2008a).…”
Section: Contributementioning
confidence: 99%
“…This has resulted in a situation where trade-offs are overshadowed by questions of data shortage and expertise (Hedelin 2008a;Hedelin and Lindh 2008). (Hedelin and Lindh 2008;Hedelin 2015b).…”
Section: Contributementioning
confidence: 99%
See 1 more Smart Citation